Interleukin‐6 and interleukin‐6 receptor expression, localization, and involvement in pain‐sensing neuron activation in a mouse intervertebral disc injury model. Issue 10 (29th May 2015) - Sainoh, Takeshi; Orita, Sumihisa; Miyagi, Masayuki; Sakuma, Yoshihiro; Yamauchi, Kazuyo; Suzuki, Miyako; Kubota, Go; Oikawa, Yasuhiro; Inage, Kazuhide; Sato, Jun; Fujimoto, Kazuki; Shiga, Yasuhiro; et al.
ABSTRACT The pathological mechanism of intractable low back pain is unclear. However, intervertebral disc (IVD) degeneration is a primary cause of low back pain, and pain‐related mediators, such as interleukin‐6 (IL‐6), have been correlated with discogenic pain. The objective of this study is to elucidate the mechanism of local IL‐6 and IL‐6 receptor (IL‐6R) expression after IVD injury as well as determine the involvement of IL‐6/IL‐6 signaling in discogenic pain. To do this, quantitative and immunohistological analyses in a mouse model of IVD injury were performed. Firstly, we measured the local expression levels of IL‐6 and IL‐6R in IVDs by enzyme‐linked immunosorbent assay (ELISA). Secondly, we immunohistochemically confirmed their localization in injured IVDs. Lastly, we evaluated the effects of intradiscal injection of an IL‐6 inhibitor by evaluating pain‐related protein, calcitonin gene‐related peptide (CGRP), expression in dorsal root ganglia (DRG) neurons that innervate IVDs. Injured IVDs showed increased production of IL‐6 and IL‐6R. IL‐6 and IL‐6R expression in the injured IVD were predominantly localized in the annulus fibrosus and endplate, and intradiscal injection of the IL‐6 inhibitor suppressed CGRP expression in the DRG neurons. These results show that IL‐6 and IL‐6R expression levels are responsive to IVD injury and that inhibition of IL‐6/IL‐6R signaling may be a promising analgesic treatment for degenerative disc diseases. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1508–1514, 2015.